Professional Development of Secondary School English Language Teachers During and After COVID-19 Pandemic - Haque, Md. Mominul; Al-Mamun, Abdullah (English Language Teaching Perspectives, 2025)
This study investigates perceptions and practices of secondary level English teachers during and after the COVID-19 driven distant education period and explores the skills that secondary level English teachers had to acquire to meet the online distance teaching needs during COVID-19 pandemic and the ones that are still in use in the post-pandemic teaching conditions. Ten secondary level English teachers were selected for this mixed-method study. The results show that the teachers mostly had to develop their Technological Knowledge (TK) which indirectly added to their Pedagogical Knowledge (PK); no direct attempts were made to improve their PK or the Content Knowledge (CK). Their responses indicate that the teachers did not feel to work on their CK. The study has a number of implications, including the need for teacher education programs to increase teacher awareness of new pedagogical-technological learning methods and the significance of providing opportunities for teachers to acquire digital competence and encourage them to adapt personally to new digital technologies within specific disciplinary contexts. The findings have both theoretical and practical implications for pre-service and in-service teacher training programs in order to satisfy the requirements of the post-pandemic English language teaching environment.